Revitalizing the heart: strategies and tools for cardiomyocyte regeneration post-myocardial infarction - Axelle Bois; Catarina Grandela; James Gallant; Christine Mummery; Philippe Menasché (npj Regenerative Medicine)
Abstract Myocardial infarction (MI) causes the loss of millions of cardiomyocytes, and current treatments do not address this root issue. New therapies focus on stimulating cardiomyocyte division in the adult heart, inspired by the regenerative capacities of lower vertebrates and neonatal mice. This review explores strategies for heart regeneration, offers insights into cardiomyocyte proliferation, evaluates in vivo models, and discusses integrating in vitro human cardiac models to advance cardiac regeneration research.